The locked garden - Whelan, Gloria (HarperCollinsPublishers, 2009)
After their mother dies of typhoid, Verna and her younger sister Carlie move with their father, a psychiatrist, and stern Aunt Maude to an asylum for the mentally ill in early-twentieth-century Michigan, where new ideas in the treatment of mental illness are being proposed, but old prejudices still hold sway.